(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2018)
Fetus and fetu is a rare mysterious medical phenomenon in which an acardiac fetiform mass is commonly located in abdomen of a neonate or infant. We report on a case of a 7 month-old girl with a gradually enlarging right upper abdominal mass and progressive jaundice, whose plain abdominal radiograph, ultrasonography, and computed tomography scan revealed a mass in which the contents favor a fetus in fetu. Obstructive jaundice was caused by billiary obstruction by FIF . Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (2): 61-65